Seronegative Coeliac Disease in Children: A Case Report and Review of the Literature - Vinod Kolimarala; Ekta Vasita; Hany Banoub; Sonny K. F. Chong (Hindawi Limited, 2017)
Serology is frequently used for the diagnosis of coeliac disease in children; however, a small proportion of children are seronegative. We present a case of seronegative coeliac disease along with literature review to include diagnostic and management dilemmas.